The utility of anthopometric indicators to identify cardiovascular risk factors in Vietnamese children. Issue 9 (22nd January 2020) - Mai, T. M. T.; Gallegos, D.; Jones, L.; Tran, Q. C.; Tran, T. M. H.; van der Pols, J. C.
Abstract: BMI, waist circumference (WC) and waist-to-height ratio (WHtR) can be used for discriminating children and adolescents at risk of CVD. However, consensus on how to use these anthropometric indicators is lacking for children and adolescents in Asia. Discrete criteria are promoted internationally, but continuous variables could be used. Data from a survey of 10 949 Vietnamese school-aged children (6–18 years) were used to evaluate the performance of anthropometric indicators to identify elevated blood pressure (BP), dyslipidaemia or at least three cardiovascular risk factors (CVRF). Weight, height, WC and BP were measured using standardised protocols; 1009 participants who had blood lipids were analysed. AUC was used to assess the performance, and the Youden index to identify optimal cut-offs. The prevalence of elevated BP, dyslipidaemia and CVRF was 26·5, 49·3 and 12·2 %, respectively. BMI, WC and WHtR had low capacity to identify elevated BP and dyslipidaemia (AUC range 0·61–0·66) but moderate capacity to identify CVRF (0·72–0·74). Optimal BMIZ cut-offs to identify elevated BP, dyslipidaemia and CVRF were 0·40, 1·01 and 1·1 sd ; for WC z -score, they were 0·06, 0·49 and 0·62 sd ; for WHtR, optimal cut-offs were close to 0·5. A BMIZ cut-off of 1·0 sd and a WHtR cut-off of 0·5 would, therefore, be useful criteria to identify Vietnamese children who are likely to have CVRF. However, further validation of these criteria in other studies of Asian children and adolescents is needed.